Attitudes and applications of chairwork amongst CBT therapists: a preliminary survey. (15th July 2021) - Pugh, Matthew; Bell, Tobyn; Waller, Glenn; Petrova, Emma
Abstract: Chairwork refers to a collection of experiential interventions which utilise chairs, their positioning, movement, and dialogue to facilitate therapeutic change. Chair-based methods are used in several models of psychotherapy, including cognitive behavioural therapy (CBT). However, little is known about cognitive behavioural therapists' use and attitudes towards chairwork. A mixed methods survey was conducted of 102 therapists who provided CBT. Overall, training in chairwork was weak amongst CBT therapists (35%). Quantitative results indicated that most therapists perceived chairwork to be clinically effective and consistent with the cognitive behavioural model, but did not feel competent using these methods. Perceived competence was highest amongst therapists who had been trained in chairwork and practised it frequently, but was unrelated to CBT accreditation or clinical experience. Qualitative feedback identified a number of factors that encouraged the use of chairwork (e.g. overcoming limitations associated with verbal restructuring methods), as well as inhibitors (e.g. therapist anxiety and limited access to training). These preliminary findings highlight a need for further research relating to cognitive behavioural chairwork and suggest that increased training in experiential interventions could go some way towards improving outcomes in CBT. Key learning aims: As a result of reading this paper, readers should: (1) Understand cognitive behavioural therapists' attitudes towards chairwork. (2) Appreciate therapists' anxiety and avoidance in relation to chairwork. (3) Identify the key factors that facilitate or inhibit the use of cognitive behavioural chairwork.